A CRITICAL ANALYSIS OF NASAPRATINAHA IN RELATION TO CONTEMPORARY CONCEPT OF NASAL OBSTRUCTION - Sarmah, *Jyotirmoy; Mahanta, Hareswar; Rekha Sarma, Dipti (AYUSHDHARA, 2016)
Nasal obstruction or blocked nose or stuffy nose is a common problem seen in E.N.T. as well as general practice. Patients visit the doctors with varying conditions of nasal obstruction- unilateral or bilateral, incomplete or complete, temporary or persistent etc. along with various others associated complaints. Depending on the causes of nasal obstruction, management also varies; which ranges from behavioural changes (i.e. avoiding exposure to inciting factors) and use of oral as well as topical drugs to invasive surgeries. The treatment can thus be medical or surgical. The existing treatment practices have their own merits and demerits, indications and contraindications, recurrences and complications etc. too, and accordingly the outcome differs. While relief is seen in many, many others have to live with a persistent stuffy nose throughout their life. In Ayurveda, detailed description of diseases of nose is found, under the broad heading of ‘Nasa Rogas’. Among these ‘Nasanaha’ or ‘Nasapratinaha’ is an important entity which is characterized by the clinical features of blocked nose. Ayurvedic Acharyas, have described about ‘Nasapratinaha’ along with the management in their texts. A systematic literary review of the Ayurvedic literature regarding ‘Nasapratinaha’ along with the various disease entities of contemporary science having similar presentations have been conducted in this study.